(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2014)
Correct age determination is of great relevance in legal prosecution. The principal means that enable one to form a fairly accurate opinion about the age of an individual are general physical development, dentition, secondary sex characters and ossification of bones. Among them, radiological examination of the ossification process is most accurate than any other method, up to the age of 20 years. This study involves radiological examination of the pelvis (Antero-posterior view) of 169 individuals to study the age-related appearance and fusion of ossification centre of ischial tuberosity in both male and female subjects aged 14-22 years at the SP Medical college, Bikaner, Rajasthan.